(untitled) (Research, Society and Development, 2022)
The Curriculum Component of Religious Education in Brazilian public schools opens possibilities to approach the religious phenomenon, including the different religious expressions present in the school space. The article presents as a general objective to highlight that, although Religious Education favors dialogue on cultural and religious diversity, the challenges in publicizing some religiosities, in particular, Afro-Brazilian religions in the school environment, are still perceptible, but when proposing the theme for students is to make it possible to overcome stereotypes and combat intolerance reactions in order to guarantee the right to religious freedom. The methodology of the article is constituted as a theoretical-based bibliographic review, which guided the reflection on the importance of including Afro-Brazilian religious traditions in the school environment. It is concluded that the Curricular Component of Religious Education enables the promotion of a dialogic space addressing the various religiosities, including Afro-Brazilian religions without causing discomfort in the school community, promoting respect for the religious freedom of children and adolescents, causing students to new look at religious traditions, leading them to the exercise of tolerance, and banking inauthentic concepts coming from long generations.